2018
DOI: 10.1680/jgeot.16.p.245
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation into the micromechanics of non-active clays

Abstract: The paper presents an experimental investigation into the micro-mechanisms controlling the behaviour of non-active clays. Clay microstructural behaviour was investigated via Mercury Intrusion Porosimetry accompanied by Scanning Electron Microscope images. To gain insight into the mechanisms underlying reversible and non-reversible compression, samples for MIP testing were taken along both normal compression and unloading-reloading lines. To investigate the nature of inter-particle forces, the response of clay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 36 publications
(48 reference statements)
6
51
0
Order By: Relevance
“…Thus, within an alkaline solution the resulting in a net negative charge on the edge's surface. Pedrotti (2016) reported that it is common practice to use potassium hydroxide KOH or similar to raise the pH of the solution in order to assess the edge charges. Sodium hexametaphosphate, (NaPO 3 ) 6 , is also known to Thus, when kaolin is mixed with distilled water (pH7), the pH of the mixture is found to be somewhere below 5.…”
Section: -Characteristics Of Surface Chargesmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, within an alkaline solution the resulting in a net negative charge on the edge's surface. Pedrotti (2016) reported that it is common practice to use potassium hydroxide KOH or similar to raise the pH of the solution in order to assess the edge charges. Sodium hexametaphosphate, (NaPO 3 ) 6 , is also known to Thus, when kaolin is mixed with distilled water (pH7), the pH of the mixture is found to be somewhere below 5.…”
Section: -Characteristics Of Surface Chargesmentioning
confidence: 99%
“…On the contrary, as mentioned before, when kaolin is mixed with very alkaline solutions (e.g., KOH) its particle edges are charged negatively and pH > 6. Figure 2.7 -Surface charges on Kaolin particles (after Pedrotti, 2016)…”
Section: -Characteristics Of Surface Chargesmentioning
confidence: 99%
See 3 more Smart Citations